Consumer evaluation of brand extensions - Ning, Jessie Ting Ay (2000)
Brand extension has become one of the most important topics in branding research in the 1990's. This study was conducted to obtain insights on how consumers evaluate a brand extension and form attitudes toward the brand extension. The theoretical framework used in the study was adopted from the previous research done by Aaker and Keller (1990), i.e. attitude toward the brand extension was higher when there was a perception of "fit" between the original brand and its brand extension. A survey was carried out in Klang Valley areas by using drop-off self-administered method. The researcher distributed 300 questionnaires in three major shopping malls in Klang Valley and 244 usable questionnaires were collected for the analysis. The findings of the study show that the perception of "fit" between the original brand and its brand extension is important in forming a positive attitude toward the brand extension. When the consumers perceive the original brand as a good quality product, the transfer of this perception to its brand extension will be enhanced if the perception of "fit" is high but the transfer will be inhibited if there if no perception of "fit". From the result of the analysis, it is found that consumers' evaluation and attitude toward the brand extensions is highly influenced by: the perception of overall quality of the original brand; the perception of "fit" between the original brand and its brand extension; and consumers' beliefs in the original brand.